Kontradyktoryjność w postępowaniu w sprawach o wykroczenia — założenia i praktyka - Liżyńska, Katarzyna (Wydawnictwo Uniwersytetu Wrocławskiego, 2015)
The basic assumption of the Act of 27 September 2013 amending the Act — Code of Criminal Procedure and some other acts was to make awidely understood criminal procedure, including the petty offencesprocedure more adversarial in character. The adversarial system in factsets apattern of mutual relations between partiesto the proceedings — the public prosecutor and the defendant — especially with regard to securing of equal opportunity to defend their rightsin impartial court. While an analysis of the criminal procedure indicates an actual increaseof its adversarial nature, in petty offencescasesthere can only be observed an ersatzof this process.
Keywords: postępowanie w sprawach o wykroczenia; system kontradyktoryjny; nowelizacja; inicjatywa dowodowa